Two different fatigue protocols and lower extremity motion patterns during a stop-jump task - Quammen, D.; Cortes, N.; Van Lunen, B. L.; Lucci, S.; Ringleb, S. I.; Onate, J. (Journal of Athletic Training, 2012)
Abstract: Context: Altered neuromuscular control strategies during fatigue probably contribute to the increased incidence of noncontact anterior cruciate ligament injuries in female athletes. Objective: To determine biomechanical differences between 2 fatigue protocols (slow linear oxidative fatigue protocol [SLO-FP] and functional agility short-term fatigue protocol [FAST-FP]) when performing a running-stop-jump task. Design: Controlled laboratory study. Setting: Laboratory. Patients or Other Participants: A convenience sample of 15 female soccer players (age = 19.2 ± 0.8 years, height = 1.67 ± 0.05m, mass = 61.7 ± 8.1kg) without injury participated. Intervention(s): Five successful trials of a running-stop-jump task were obtained prefatigue and postfatigue during the 2 protocols. For the SLO-FP, a peak oxygen consumption (Vo2peak) test was conducted before the fatigue protocol. Five minutes after the conclusion of the Vo2peak test, participants started the fatigue protocol by performing a 30-minute interval run. The FAST-FP consisted of 4 sets of a functional circuit. Repeated 2 (fatigue protocol) × 2 (time) analyses of variance were conducted to assess differences between the 2 protocols and time (prefatigue, postfatigue). Main Outcome Measure(s): Kinematic and kinetic measures of the hip and knee were obtained at different times while participants performed both protocols during prefatigue and postfatigue. Results: Internal adduction moment at initial contact (IC) was greater during FAST-FP (0.064 ± 0.09Nm/kgm) than SLO-FP (0.024 ± 0.06 Nm/kgm) (F1,14 = 5.610, P = .03). At IC, participants had less hip flexion postfatigue (44.7° ± 8.1°) than prefatigue (50.1° ± 9.5°) (F1,14 = 16.229, P = .001). At peak vertical ground reaction force, participants had less hip flexion postfatigue (44.7° ± 8.4°) than prefatigue (50.4° ± 10.3°) (F1,14 = 17.026, P = .001). At peak vertical ground reaction force, participants had less knee flexion postfatigue (-35.9° ± 6.5°) than prefatigue (-38.8° ± 5.03°) (F1,14 = 11.537, P = .001). Conclusions: Our results demonstrated a more erect landing posture due to a decrease in hip and knee flexion angles in the postfatigue condition. The changes were similar between protocols; however, the FAST-FP was a clinically applicable 5-minute protocol, whereas the SLO-FP lasted approximately 45 minutes.